Associations Between 25-Hydroxyvitamin D and Total and γ' Fibrinogen and Plasma Clot Properties and Gene Interactions in a Group of Healthy Black South African Women - Rautenbach, Petro H.; Nienaber-Rousseau, Cornelie; de Lange-Loots, Zelda; Kruger, Iolanthé M.; Pieters, Marlien (Frontiers in Cardiovascular Medicine, 2022)
The role of 25-hydroxyvitamin D [25(OH)D] in reducing the risk of cardiovascular disease (CVD) has been recognized, but the mechanisms involved are unclear. Researchers have discovered a link between vitamin D and fibrinogen. Until now, data on the relationship between vitamin D and the γ' splice variant of fibrinogen and fibrin clot characteristics remain unexplored. In this study, 25(OH)D, total and γ' fibrinogen, as well as turbidimetrically determined plasma clot properties, were quantified, and fibrinogen and FXIII SNPs were genotyped in 660 Black, apparently healthy South African women. Alarmingly, 16 and 45% of the women presented with deficient and insufficient 25(OH)D, respectively. Total fibrinogen and maximum absorbance (as a measure of clot density) correlated inversely, whereas γ' fibrinogen correlated positively with 25(OH)D. γ' fibrinogen increased whereas maximum absorbance decreased over the deficient, insufficient, and sufficient 25(OH)D categories before and after adjustment for confounders. 25(OH)D modulated the association of the SNPs regarding fibrinogen concentration and clot structure/properties, but did not stand after correction for false discovery rate. Because only weak relationships were detected, the clinical significance of the findings are questionable and remain to be determined. However, we recommend vitamin D fortification and supplementation to reduce the high prevalence of this micronutrient deficiency and possibly to improve fibrinogen and plasma clot structure if the relationships are indeed clinically significant. There is a need for large cohort studies to demonstrate the relationship between vitamin D and cardiovascular and inflammatory risk factors as well as to uncover the molecular mechanisms responsible.